PELAKSANAAN UPACARA BALIYA JINJA DALAM ADAT SUKU KAILI - Rosnita, Rahma (JURNAL ILMU BUDAYA, 2021)
The Baliya Jinja traditional ceremony carried out by the Kaili people will discuss what is contained in the ceremony. Baliya Jinja for the people of the Kaili Tribe is a non-medical ritual healing ceremony and has been known for hundreds of years. For the Kaili people, this ceremony is not just a traditional routine, but substantially has its own meaning through an integrated system. Through semiotic analysis with the theory used by Ferdinand de Saussure, it can be seen that the Baliya Jinja traditional ceremony applied to the Kaili Tribe is a contextual language system that clearly contains certain meanings. The elements that make up the Baliya Jinja ceremony to be meaningful are of course the sign system as a symbol, grammar. The Baliya Jinja ceremony for the Kaili people will be described through a syntagma and system study.